2002
DOI: 10.1097/00004032-200202000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Exposure Rates Under Inclined Birch Trees Indicate the Occurrence of Rainfall During Radioactive Fallout From Chernobyl

Abstract: Knowledge of the mode of deposition (wet or dry) during the main fallout period following the Chernobyl accident in late April 1986 is one of the most important parameters in environmental reconstruction of the radiation dose to the thyroid from 113I following the accident. Meteorological data are available only for a small number of locations, but routine field measurements in 1997 of exposure rates in areas still contaminated by 137Cs revealed that there is a natural indicator of wet deposition. Follow-up me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…It has been reported that dry deposition from the Chernobyl accident has led to local 137 Cs ground contamination levels of as much as 1 MBq m ÿ2 in the settlement of Vishkov in the Bryansk region, about 160 km away from the Chernobyl NPP (Stepanenko et al, 2002). Significantly smaller dry contamination levels have been reported for other areas in the Bryansk region, but the choice of this round figure for the contamination level on the reference surface facilitates the scaling of the results of the case study.…”
Section: General Case Study Assumptionsmentioning
confidence: 99%
“…It has been reported that dry deposition from the Chernobyl accident has led to local 137 Cs ground contamination levels of as much as 1 MBq m ÿ2 in the settlement of Vishkov in the Bryansk region, about 160 km away from the Chernobyl NPP (Stepanenko et al, 2002). Significantly smaller dry contamination levels have been reported for other areas in the Bryansk region, but the choice of this round figure for the contamination level on the reference surface facilitates the scaling of the results of the case study.…”
Section: General Case Study Assumptionsmentioning
confidence: 99%
“…Rainfall can strongly increase radiation on the ground ( Pietrzak-Flis et al 2003 ; Rosner et al 1990 ; Stepanenko et al 2002 ). The most radioactive cloud, accompanied by strong rain, passed above the eastern part of the Czech Republic on 30 April and 1 May 1986 ( Kunz 1986 ).…”
mentioning
confidence: 99%